입도분포와 다짐에너지의 변화에 따른 흙의 다짐 및 투수특성 - 백승환; 윤성욱; 박진철; 유찬 (농업생명과학연구, 2007)
흙의 입도분포에 따른 다짐과 투수특성에 대한 연구를 수행하였다. 이러한 특성은 단층형 매립지에서 단층형 최종복토공법의 설계에서 매우 중요한 설계인자이다. 실험에서는 모래와 실트질 흙을 중량 기준으로 80:20. 70:30 그리고 60:40으로 혼합하고 각각의 혼합된 경우에 대해서는 표준다짐(A-1)을 실시하였는데, 이때 각층의 다짐회수를 5, 10, 15, 20 그리고 25회로 조절하여 실시하였다. 다짐된 시료에 대해서는 최대건조단위중량과 최적함수비의 변화와 투수계수의 변화를 관찰하였다. 실험결과, 세립분 함유량 18.5%이상으로 유지되고 가벼운 다짐을 실시해줌으로 단층형 최종복토공법에서 적용 가능한 범위의 건조단위중량과 투수계수가 얻어질 수 있는 것으로 판단되었다. Laboratory tests were carried out to investigate the variation of compaction characteristics and permeability of soils with the particle distribution. These properties is important factors for the design of the mono-layer landfill final cover system. In compaction tests, two types of soil, especially sand and silt, were mixed each other in the ratio of 80:20, 70:30, 60:40 in the weight base and the number of blow of rammer was controled to 5, 10, 15, 20 and 25 in each layer. Variations of maximum dry density and optimum water content were observed and adapted to the permeability tests to investigate the variation of coefficient of permeability. KCI Citation Count: 1